Abnormal Expression of Dysferlin in Blood Monocytes Supports Primary Dysferlinopathy in Patients Confirmed by Genetic Analyses - Zhang, Huili; Li, Yaqin; Cheng, Qiusheng; Chen, Xi; Yu, Qiuxia; Li, Ze (Frontiers in Neurology, 2021)
Objective: Dysferlin deficiency causes dysferlinopathies. This study aimed to expand the mutational spectrum of dysferlinopathies and , to further study one case with diagnostic ambiguity and to identify the diagnostic value of dysfelin expression in total peripheral blood mononuclear cells (PBMC). Methods: The clinical and molecular profiles of dysferlinopathies in eight Chinese patients were evaluated. We also conducted magnetic resonance imaging (6/8), and determined dysferlin protein expression in muscle (7/8) and PBMC (3/8). Results: Nine of the 13 DYSF mutations identified were novel. One patient was homozygous for the Gln111Ter mutation by genomic DNA sequencing, but was found to be heterozygous by sequencing of cDNA from total PBMC. A daughter of this patient did not carry any Gln111Ter mutation. Abnormal muscle MRI with predominant involvement of the medial gastrocnemius and soleus muscle was observed in 5/6 patients. Dysferlin levels were significantly reduced (immunohistochemistry/immunblot) or absent (immunohistochemistry) in muscle and total PBMC (26% to 39%) for most patients. Sarcoplasmic accumulation of dysferlin was detected in one patient. Conclusion: Genomic DNA sequencing detects frequent homozygous mutations, while fewer heterozygous mutations in cDNA are detected after post-transcription . Total PBMC may serve as an alternative to confirm diagnosis andor to guide further testing in dysferlinopathies. Our results contribute to the mutational spectrum of dysferlinopathies.